A Novel Circular Plate Acoustic Energy Harvester for Urban Railway Noise - Tian-Chen Yuan; Fei Chen; Jian Yang; Rui-Gang Song; Yong Kong (Shock and Vibration)
To harvest acoustic energy from urban railways, a novel and practical acoustic energy harvester is developed. The harvester consists of a piezoelectric circular plate and a Helmholtz resonator. Based on the field test data of urban railways, the resonance frequencies of the piezoelectric circular plate and the Helmholtz resonator are near 800 Hz. The Helmholtz resonator is designed to amplify the sound pressure. Thus, a lumped parameter model is established. The piezoelectric circular plate is used to convert mechanical energy into electrical energy. The simulation results show that the output power of the harvester is approximately 25 μW and the maximum voltage is 0.149 V under the excitation of urban railway noise. The experiment device is also developed. The maximum output power of the harvester is 8.452 μW, and the maximum voltage is 0.082 V. The experimental and the numerical results are in good agreement and demonstrate the effectiveness of the proposed acoustic energy harvester.